Melt blown polypropylene nanofiber template for homogenous pore channels monoliths - Zykamilia Kamin; N Abdulrahim; Mailin Misson; C Chel Ken (2020)
Monoliths are an important technology for filtration, liquid chromatography, and protein purification. A template commonly uses to produce porous monolith. However, it is a challenge to produce a monolith with a homogenous porous structure due to the arrangements of pores within the monolith are often uneven and sometimes closed, causing pressure to accumulate and increase within the monolith which reduce the efficiency of the monoliths. Therefore, an appropriate template is needed to produce a monolith with homogenous porous structure. Nanofiber is a potential alternative as a template due to its high porosity and interconnectivity. Therefore, this research aimed to investigate the potential of polypropylene melt blown nanofiber fabricated at various operating condition to fabricate monolith by assessing the monolith morphology. Nanofibers templates were produced using a melt blowing technique at various motor speeds, air pressures, and die-to-collector distance (DCD) between 30 and 50 Hz, 0.30 and 0.50 Mpa, and 20 and 50 cm respectively, design by Response Surface Methodology. The nanofibers were characterized for its morphology and melting point using scanning electron microscope (SEM) and molten point analysis instrument respectively. The findings show that the polypropylene nanofiber diameter was in the range of 3.58 to 11.00 x 103 nm. Meanwhile, melting point obtained were in the range of 121.0 to 128.8 °C. Subsequently macropores monoliths were successfully fabricated at 0.45 Mpa air pressure, 40 Hz motor speed and 60.23 cm die-to-collector distance. It can be concluded that, melt blown polypropylene nanofiber can be potentially applied as a template for monolith fabrication.